2007
DOI: 10.1111/j.1523-5378.2007.00563.x
|View full text |Cite
|
Sign up to set email alerts
|

The Long‐term Impact of Helicobacter pylori Eradication on Gastric Histology: a Systematic Review and Meta‐analysis

Abstract: The results showed significant improvement of GA, whereas improvement was not shown for IM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
136
1
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(154 citation statements)
references
References 31 publications
8
136
1
9
Order By: Relevance
“…The study reported that mass eradication of H.pylori was effective in significantly reducing the incidence of gastric atrophy resulting from chemoprevention (77.2%; 95% CI 72.3%-81.2%), although the reduction in incidence of intestinal metaplasia was not significant. (35) Similarly, two other meta-analyses, (36,37) which addressed the controversial issue regarding the impact of H. pylori eradication on gastric atrophy and intestinal metaplasia, showed significant improvement in gastric atrophy but not gastric intestinal metaplasia. Thus, gastric intestinal metaplasia is generally regarded as the point of irreversible histological change.…”
Section: H Pylori and Gastric Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The study reported that mass eradication of H.pylori was effective in significantly reducing the incidence of gastric atrophy resulting from chemoprevention (77.2%; 95% CI 72.3%-81.2%), although the reduction in incidence of intestinal metaplasia was not significant. (35) Similarly, two other meta-analyses, (36,37) which addressed the controversial issue regarding the impact of H. pylori eradication on gastric atrophy and intestinal metaplasia, showed significant improvement in gastric atrophy but not gastric intestinal metaplasia. Thus, gastric intestinal metaplasia is generally regarded as the point of irreversible histological change.…”
Section: H Pylori and Gastric Cancermentioning
confidence: 99%
“…Thus, gastric intestinal metaplasia is generally regarded as the point of irreversible histological change. (36,37) Uemura et al, (38) who were the first to provide evidence that H. pylori eradication has a direct impact on gastric cancer occurrence, conducted a non-randomised H. pylori eradication trial in patients with early gastric cancer treated by endoscopic resection. After a three-year follow-up period, 9% of the untreated patients developed metachronous gastric cancer, while none of the patients who underwent H. pylori eradication developed the disease.…”
Section: H Pylori and Gastric Cancermentioning
confidence: 99%
“…These cells are easily identified in the gastric mucosa since they are not present in the normal gastric mucosa and their identification presents high inter-observer agreement (18) . Although it also presents discordant studies, different studies and meta-analysis have been unable to demonstrate intestinal metaplasia regression after H pylori eradication (113,121,153,172,203,213) .…”
Section: Statement 16mentioning
confidence: 99%
“…This result indicates that inhibitors of ADP ribosylation, for which safety data are now available due to their extensive testing in trials of metastatic breast and other cancers (19,20), might be useful compounds for the treatment of symptomatic H. pylori-infected patients. Most patients presenting with atrophic gastritis, metaplasia, or dysplasia are routinely subjected to eradication therapy targeting the underlying infection; however, eradication is only partly efficient in reversing atrophy and fails in the treatment of metaplasia and dysplasia (29). As patients with any of these conditions have an at least 10-fold increased risk of developing gastric cancer compared with histologically unapparent infected individuals, and are currently subjected to an unsatisfactory watch-and-wait strategy, there is a clear unmet need for new treatment options for this patient group.…”
Section: Discussionmentioning
confidence: 99%
“…S3C and D), indicating that Helicobacter eradication and the inhibition of ADP ribosylation have comparable effects in mice. In contrast, eradication therapy typically fails to cure the human counterpart lesions (29), suggesting that the consecutive treatment with antibiotics and ADP ribosylation inhibitors would have a beneficial effect over eradication therapy alone in humans.…”
Section: Inhibition Of Adp Ribosylation By Pj34 Reverses Preexisting mentioning
confidence: 99%